2018
DOI: 10.1017/aer.2018.50
|View full text |Cite
|
Sign up to set email alerts
|

Ice accretion and release in fuel systems

Abstract: Following the B777 accident at Heathrow in 2008, the certification authorities required Boeing, Airbus, and Rolls-Royce to conduct icing analysis and tests of their Rolls-Royce Trent engined aircraft fuel systems. The experience and the test data gained from these activities were distilled and released by Airbus to the EASA ICAR project for research and analysis. This paper provided an overview of the Airbus ice accretion and release tests. Brief narratives on the test rigs, the test procedure and methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The standard Airbus water introduction method is described by Ref. (17) and was adopted with slight modifications for this project. This method requires thorough mixing of calculated volumes of water and fuel at room temperature using an ultrasonic bath, and eventually introducing it into the system before cooling begins; at this stage, the bulk fuel temperature was set to 28 • C. No water was added after cooling commenced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard Airbus water introduction method is described by Ref. (17) and was adopted with slight modifications for this project. This method requires thorough mixing of calculated volumes of water and fuel at room temperature using an ultrasonic bath, and eventually introducing it into the system before cooling begins; at this stage, the bulk fuel temperature was set to 28 • C. No water was added after cooling commenced.…”
Section: Methodsmentioning
confidence: 99%
“…Water solubility, water settling and ice formation, amongst others, are some such properties of interest [10,11]. The behaviour of water and ice in AFS has been studied from different perspectives [3,[12][13][14][15][16][17][18]. This has resulted in a large number of systems being employed for preventing the build-up of ice in AFS [19][20][21].…”
Section: Background To Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Maloney et al explained that stainless steel accumulated more ice than roughened aluminium and Teflon, as seen in figure 10 [12]. Similarly, a recent study by Airbus on the ice accretion/release test in a large scale flowing fuel system indicated the non-uniformity of ice thickness and porosity and suggested that it is a result of water injection/mixing method [146]. Therefore, it can be concluded that the variation in reported data throughout the literature can be attributed to different testing conditions and experimental techniques.…”
Section: Effect Of Material/ Surfaces On Nucleation Of Icementioning
confidence: 98%
“…The microbial fungus appears as sludge that restricts flow at not only the fuel pump filters, but other components in the fuel system, such as valves and pipelines. More information on blockages caused by ice for aircraft can be found in the work by Lam & Woods (2018) and by Lawson, Baena & Lam (2012). More information on blockages caused by microbial growth can be found on the book by Langton et al (2009).…”
Section: Blockagementioning
confidence: 99%